Selection of somaclonal variants of maracuyá (passiflora Edulis var Flavicarpa. Deneger) tolerants to water deficit - Iván Darío Loaiza Campiño (Revista Colombiana de Biotecnología, 2020)
Climate change will have an impact on the Colombian agricultural sector, by 2050 increases in temperature and distribution of erratic rainfall are expected. Passion fruit cultivation does not tolerate water deficit, it reduces flower induction, generates fruit drop and defoliation. To tackle this problem, somaclonal variants (VS) of passion fruit were selected in-vitro, seeking tolerance to water deficit. Four phases were developed: I) callogenesis, II) direct and indirect organogenesis, II) Induction and evaluation of the water deficit with Polyethylene glycol 6000 (PEG 6000) and IV) in vitro selection of VS by morphometric measurements, chlorophyll and total sugars contents. Differences in callogenesis were found with different concentrations of 2,4-D, the concentration of 2 mg L-1 presented better results producing calluses in less time and in greater quantity (8 days, 90% of the leaf area). In indirect and direct organogenesis the medium MS + ANA + BAP (0.3: 0.6), showed significant statistical differences with respect to other means, for the variables root length (15.14 cm), stem (16.72 cm) and leaves ( 14.51 cm) and root thickness (0.76 cm) stem (1.25) and leaf width (6.75). The influence of PEG 6000 showed significant differences, the treatment with 30 g L-1 showed the smallest leaf width, the greatest width was found in 25 g L1. Statistical differences were found in chlorophyll levels and total sugar contents, the highest contents were recorded in the VS 25VS1, showing the possibility of obtaining seedlings tolerant to the water deficit of passion fruit by inducing somaclonal variation.